Deep learning-based automatic document categorization and organization - Foo, Shawn Nicholas Say Yan (Nanyang Technological University, 2021)
Given the vast improvement in information technology today, document classification has become a major research area of Natural Language Processing. Previously, document classification was done by using Traditional Machine Learning algorithm to categorize online documents. However, Traditional Machine Learning algorithms have shown to be unable to cope with the massive amount of online information generated daily. On the other hand, Deep Learning algorithms’ performance increases with data. Therefore, we introduce Deep Learning models to perform the document classification task, using the large amount of information data being generated daily.